Tri Hita Karana and Economic Ethics: Cultural Foundations of Community-Based Financial Institutions in Bali (International Journal of Social Studies, 2026)
This study examines Tri Hita Karana as a cultural and ethical foundation of Village Credit Institutions (Lembaga Perkreditan Desa LPD) in Bali, addressing the gap in existing financial sustainability literature that has largely emphasize technical governance while neglecting indigenous moral frameworks. This study adopts a qualitative interpretive approach supported by a conceptual-analytical framework and synthesis of prior empirical studies, including those employing SEM-PLS. It explores how the principle of parahyangan, pawongan, and palemahan are institutionalized through the ethical constructs of Karma and Dharma in shaping financial performance and long-term sustainability. Data were derived from a structured literature review, customary village regulations, and previous ethnographic and empirical studies, analyzed using thematic coding, institutional mapping, and interpretive synthesis. The findings indicate that Karma and Dharma strengthen financial performance by enhancing spiritual accountability, social trust, and ethical discipline. Furthermore, financial performance mediates their influence on institutional sustainability. These results suggest that Tri Hita Karana operates not merely as a cultural philosophy but as an applied system of economic ethics that translates moral values into financial resilience. This study contributes to the literature by demonstrating that culturally embedded Hindu ethics constitute a form of institutional capital and offer an alternative framework for integrating economic, social, and environmental sustainability in community-based finance.